PREDICTORS OF A LOCAL RECURRENCE AFTER ORGAN-PRESERVING TREATMENT FOR EARLY BREAST CANCER: STATE-OF-THE-ART - N. R. Molodikova; M. I. Nechushkin; V. A. Uimanov; A. V. Trigolosov; M. V. Chernykh; N. V. Bekuzarova (Опухоли женской репродуктивной системы)
There are currently many unsolved problems associated with the optimization of treatment in patients with breast cancer (BC) who have undergone organ-preserving operations. The occurrence of BC recurrences after organ-preserving treatment, their determination and prognostic factors are a challenge.